An expanded description of Cnemaspis gracilis (Beddome 1870) (Squamata: Gekkonidae) based on recent material - Khandekar, Akshay; Gaikwad, Sunil M.; Pal, Saunak; Thackeray, Tejas; Agarwal, Ishan (Zootaxa, 2023)
Cnemaspis gracilis is a poorly known species that has been reported from across southern India, with 11 named species within the clade. The species is known only from the type series, as many other records from areas outside the type locality have turned out to represent distinct species. We provide an expanded morphological description of the species based on topotypic material and other samples that were assigned using genetic data. Cnemaspis gracilis is now known with certainty from three localities in the vicinity of Palakkad, Palakkad District, Kerala, and Valparai town, Coimbatore district, Tamil Nadu, besides from an introduced population in the Timber Market, Kolhapur city, Kolhapur district, Maharashtra, India. The species is 7.6–15.8 % divergent on the ND2 gene from described members of the gracilis clade and can be diagnosed by a combination of morphological characters including body size, number of paravertebral tubercles between limb insertions, number of dorsal tubercle rows, number of ventral scale rows across the belly, number of femoral and precloacal pores and poreless scales separating these series in males, and the presence of a single central black ocellus on the neck and a smaller one on the occiput. The assignment of extant populations to the species, a detailed morphological description and genetic data will allow the description of many more species from within this diverse clade of diurnal geckos.